Hazards and Control Measures among Artisanal and Small-Scale Gold Miners in Zimbabwe - Josephine Singo; John Bosco Isunju; Dingani Moyo; Nadine Steckling-Muschack; Stephan Bose-O'Reilly; Antony Mamuse (Ubiquity Press, 2022)
Background: In 2017 around 14-19 million miners were exposed to multiple hazards in artisanal and small-scale gold mining (ASGM). ASGM is characterized by basic and compromised mining methods with either very limited control of hazards or none at all. There is little knowledge about health and safety among artisanal and small-scale gold miners in Zimbabwe. Objective: This study explores the interaction between hazards, control measures, and health and safety in Zimbabwe's ASGM. Methods: Triangulation and mixed methods were applied using standardized questionnaires, Hazard Identification and Risk Assessment (HIRA), focus group discussions (FGDs), and summary notes from in-depth interviews (IDIs). Data were analyzed using descriptive statistics, regression analysis, and thematic analysis. Findings: Quantitative data were collected through HIRA, which was conducted on 34 mining sites. 401 participants, selected through multi-stage sampling, were assessed through standardized questionnaires. Qualitative data was collected through six FGDs, and existing summary notes from 84 IDIs. The most prioritized hazards from the questionnaires were silica dust, noise, and workplace violence as indicated by 238 (62.0%), 107 (26.8%), and 104 (26.7%) respondents (respectively). HIRA identified noise, dust, unsafe shafts, violence, poor sanitation, and poor hygiene as key hazards requiring urgent attention. A key finding of this study was the poor application of the hierarchy of controls in managing workplace hazards. After adjusting for confounders, association with experiencing health and safety challenges was working underground (AOR = 2.0, p = 0.03), workplace violence (AOR = 3.3, p = 0.002), and long working hours (AOR = 2.8, p = 0.019). Injuries and fatalities were common without mitigation strategies. Conclusions: ASGM in Zimbabwe is characterized by underground mining, long working hours, and workplace violence. The poor application of the hierarchy of controls is characterized by increased workplace injuries and fatalities. We recommend following the hierarchy of control measures in ASGM: elimination, substitution, engineering, administrative, and personal protective equipment.